Preparation method, product and application of biochar-based catalyst
By combining antibiotic waste residue with the precursor substances of Mn and metal N, a biochar-based catalyst was prepared, which solved the problem of low efficiency and poor stability of antibiotic waste residue-derived catalytic materials, and achieved efficient SCR reaction and good anti-toxicity performance.
Patent Information
- Application Number
- CN202411306857.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-09-19
AI Technical Summary
Due to the lack of active sites, disordered matrix and complexity of inherent components, existing antibiotic waste residue-derived catalytic materials have low catalytic efficiency and poor stability, making it difficult to meet the deep demand for the coexistence of multiple pollutants under complex operating conditions.
Biochar-based catalyst was prepared by combining antibiotic waste residue with precursor substances of Mn and metal N. The method includes mixing the homogeneous solution with the alkaline solution, filtration, washing and calcining after aging, obtaining a hydrotalcite-like composite material containing N, Mn and antibiotic waste residue, and finally preparing a biochar based catalyst.
The high dispersion of active metal species at the atomic level is achieved, the density of surfactant oxygen species and acidic site of the catalyst is improved, the excellent redox capacity is excellent, the NH3-SCR reaction is promoted, and the anti-toxicity and stability of the catalyst is improved.
Smart Images

Figure CN119075976B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalysts, and in particular to a preparation method, product and application of a biochar-based catalyst. Background Art
[0002] At present, environmental problems such as air pollution caused by industrialization have become urgent issues around the world. Among them, nitrogen oxides (NO x ) is a major air pollutant. To reduce emissions and maintain a high-quality living environment, regulatory measures are becoming increasingly stringent. Purification of nitrogen oxides in industrial flue gas is the most important issue in environmental protection. Among the current denitrification technologies, Selective Catalytic Reduction (SCR) technology has been widely used due to its high denitrification efficiency and relatively mature technology. SCR technology uses ammonia (NH 3 ), urea or hydrocarbons and H 2 As reducing agents, under certain temperature and catalyst, NO in flue gas can be selectively reduced to x Restore to N 2 and H 2 O. The reaction can be carried out at a temperature not higher than 400°C, and the denitrification rate can basically reach 80% to 90%. 3 –SCR technology is the most widely used due to its high efficiency.
[0003] Antibiotics have made outstanding contributions to the treatment and prevention of diseases, but due to their frequent and large-scale use and continuous discharge, antibiotics in the environment have been listed as an emerging environmental pollutant internationally. At present, different levels of antibiotic residues have been detected in soil, surface water and groundwater in countries around the world. Pharmaceutical companies produce a large amount of bacterial residue in the process of producing antibiotics. According to the calculation that 1 ton of antibiotic raw materials produces about 8 to 10 tons of wet bacterial residue, a large amount of antibiotic wet bacterial residue is produced every year. Antibiotic bacterial residue is unstable in nature, easy to corrupt and emit a foul odor. It can also induce bacterial resistance and antibiotic resistance genes, coerce environmental microorganisms and induce the development of drug-resistant microorganisms in the environment, posing huge safety hazards to humans and the ecological environment. In my country's latest revised "National List of Hazardous Wastes" (2021), antibiotic bacterial residues still belong to HW02 hazardous wastes.
[0004] In recent years, the application of industrial waste as a resource in the field of environmental governance and restoration is in line with the concept of "waste treatment with waste". Antibiotic waste residues are rich in organic matter, among which crude protein, crude fat and polysaccharides have high contents, and can be used as biomass resources. For catalytic materials derived from antibiotic waste residues, the lack of active sites, the disorder of the matrix and the complexity of the inherent components hinder the directional flow of electrons, resulting in low SCR catalytic efficiency and poor stability, which makes it difficult to meet the deep needs of the coexistence of multiple pollutants under actual complex working conditions. Summary of the invention
[0005] Based on the above content, the present invention provides a preparation method, product and application of a biochar-based catalyst.
[0006] To achieve the above object, the present invention provides the following solutions:
[0007] One of the technical solutions of the present invention is a method for preparing a biochar-based catalyst, comprising the following steps:
[0008] Step 1, dissolving two precursor materials containing Mn and metal N respectively in water to prepare a homogeneous solution;
[0009] Step 2, adding the homogeneous solution into the alkaline solution containing the waste residue L and maintaining the pH of the reaction system at an alkaline level, aging, and obtaining a mixed solution;
[0010] Step 3, filtering and washing the mixed solution, and then drying to obtain a hydrotalcite-like composite material containing N, Mn and L;
[0011] Step 4, calcining the hydrotalcite-like composite material containing N, Mn and L to obtain the biochar-based catalyst;
[0012] The metal N is Al and / or Fe;
[0013] The waste residue L is at least one of streptomycin waste residue, oxytetracycline waste residue and gentamicin waste residue. Further preferably, the metal N is Al, and the waste residue L is streptomycin waste residue.
[0014] The second technical solution of the present invention is a biochar-based catalyst prepared using the above-mentioned preparation method.
[0015] The third technical solution of the present invention is that the above-mentioned biochar-based catalyst selectively catalytically reduces NO in flue gas. x Application in.
[0016] The present invention discloses the following technical effects:
[0017] The present invention uses antibiotic waste residue composite hydrotalcite (LDHs) layered materials as precursors to prepare biochar-based catalysts for SCR denitrification technology, achieving high dispersion of active metal species at the atomic level, effectively adsorbing and activating NH 3 、NO x The biochar-based catalyst of the present invention can not only remove pollutants efficiently and maintain good stability, but also has high sulfur and water resistance, and the preparation method is simple and can be synthesized in one step.
[0018] The present invention uses antibiotic waste residue as biomass resources and utilizes the advantages of high dispersion, high specific surface area, and structural controllability of hydrotalcite-like active components to solve the shortcomings of the lack of active sites in biochar materials, the disorder of the matrix, and the complexity of inherent components that hinder the directional flow of electrons. A multifunctional biochar-based SCR catalyst is obtained, which can efficiently treat hazardous waste - antibiotic waste residue while improving the low catalytic efficiency, poor stability, and insufficient anti-poisoning performance of biochar-based materials.
[0019] Compared with single antibiotic waste residue-derived biochar materials and LDHs materials, the biochar-based catalyst prepared by the present invention contains more surface active oxygen species and acid sites, and has excellent redox ability, which can effectively promote NH 3 -SCR reaction, improving the anti-poisoning performance of the catalyst. In addition, the biochar-based catalyst can effectively solve the problem of handling and disposing of a large amount of waste antibiotic residues, reduce the cost of material production, and realize the rational resource utilization of antibiotic residue waste, with both economic and environmental benefits, becoming an important "carbon negative" energy strategy. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0021] Figure 1 a is an X-ray diffraction spectrum, which is respectively Mn before calcination in comparative example 2 1 Al 1 -LDH hydrotalcite (MnAl-LDH in the figure represents Mn 1 Al 1 -LDH), Mn before calcination in Example 1 1 Al 1 -LDH-Str hydrotalcite (MnAl-LDH-Str in the figure represents Mn 1 Al1 -LDH-Str), Mn obtained after calcination in Comparative Example 2 1 Al 1 O z Catalyst, Mn obtained after calcination in Example 1 1 Al 1 O z -Str-2 catalyst. Figure 1 b is the Mn after calcination in Example 1 1 Al 1 O z -TEM-EDS image of Str-2 catalyst. DETAILED DESCRIPTION
[0022] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0023] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0024] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0025] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0026] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0027] The "room temperature" described in the present invention, unless otherwise specified, refers to 20 to 30°C.
[0028] One of the technical solutions of the present invention is a method for preparing a biochar-based catalyst, comprising the following steps:
[0029] Step 1, dissolving two precursor materials containing Mn and metal N respectively in water to prepare a homogeneous solution;
[0030] Step 2, adding the homogeneous solution into the alkaline solution containing the waste residue L and maintaining the pH of the reaction system at an alkaline level, aging, and obtaining a mixed solution;
[0031] Step 3, filtering and washing the mixed solution, and then drying to obtain a hydrotalcite-like composite material containing N, Mn and L;
[0032] Step 4, calcining the hydrotalcite-like composite material containing N, Mn and L to obtain the biochar-based catalyst;
[0033] The metal N is Al and / or Fe;
[0034] The waste residue L is at least one of streptomycin waste residue, oxytetracycline waste residue and gentamicin waste residue. Further preferably, the metal N is Al, and the waste residue L is streptomycin waste residue.
[0035] In some embodiments of the present invention, the molar ratio of Mn to metal N is (0.5-2): 1. More preferably, the molar ratio of Mn to metal N is 1:1.
[0036] The concentration of the homogeneous solution and the concentration of waste residue L in the alkaline solution containing waste residue L have no effect on the performance of the prepared biochar-based catalyst. Therefore, the concentration of the homogeneous solution and the concentration of waste residue L in the alkaline solution containing waste residue L described in the present invention are not particularly limited.
[0037] In some embodiments of the present invention, the mass ratio of the precursor material containing Mn to the waste residue L is (5-6):(0.5-4). More preferably, the mass ratio of the precursor material containing Mn to the waste residue L is (5-6):2.
[0038] In some embodiments of the present invention, in step 2, the pH of the reaction system is maintained at 8 to 12, and more preferably 9.5 to 10.5.
[0039] In some embodiments of the present invention, the alkaline solution is Na 2 CO 3 aqueous solution; Mn and Na in the reaction system 2 CO 3 The molar ratio is 0.25~1.
[0040] Step 2 is carried out under the condition of isolating from air and aerating with nitrogen; the aging time is greater than 10 hours. The adding method in step 2 is dropwise addition.
[0041] The process of filtration and washing described in step 3 is specifically as follows: under filtration conditions, the mixed solution is repeatedly washed with deionized water until the pH value of the filtrate is 6-7, and when the filtrate is almost dried up, it is washed once with anhydrous ethanol, and dried to obtain a precipitate; the obtained precipitate is placed in a container filled with anhydrous ethanol, and vigorously stirred at room temperature, and then filtered, and the filter cake is repeatedly washed with anhydrous ethanol.
[0042] In some embodiments of the present invention, the calcination is specifically calcination at 350-600°C for 5 hours under oxygen-limited conditions in a muffle furnace. More preferably, the calcination temperature is 350-450°C.
[0043] The calcination is carried out in a muffle furnace. The initial calcination atmosphere is air atmosphere, but the amount of air is insufficient in the later stage of combustion. Therefore, the calcination atmosphere in the muffle furnace is called oxygen-limited conditions. The present invention finds that the catalyst obtained under oxygen-limited conditions is better than N 2 It is better under anaerobic conditions, and it must be O 2 The participation of is beneficial to the balance between the formation of metal oxygen species and biochar production.
[0044] The second technical solution of the present invention is a biochar-based catalyst prepared by the above-mentioned preparation method. The Mn in the biochar-based catalyst is Mn 2+ , Mn 3+ and Mn 4+ It exists in 2 or 3 mixed valence forms.
[0045] The third technical solution of the present invention is that the above-mentioned biochar-based catalyst selectively catalytically reduces NO in flue gas. x Application in.
[0046] In some embodiments of the present invention, the selective catalytic reduction of NO in flue gas x The reaction temperature range is 100 to 300°C, more preferably 150 to 300°C, and more preferably 150°C.
[0047] The present invention provides a solution for efficiently utilizing antibiotic waste residues and applying it to medium and low temperature SCR technology, which not only realizes the recycling of waste, but also can efficiently catalyze and reduce nitrogen oxides in flue gas at low temperatures, and also has good low temperature anti-poisoning performance and regeneration performance, which is in line with the concept of "treating waste with waste".
[0048] The technical solutions described in the present invention, unless otherwise specified, are all conventional solutions in the art, and the reagents or raw materials used, unless otherwise specified, are purchased from commercial channels or have been disclosed.
[0049] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0050] Example 1: Mn 1 Al 1 O z - Preparation method of Str-2 catalyst
[0051] (1) Add 5.81mL 50%Mn(NO 3 ) 2 Solution, 9.3783gAl(NO 3 ) 3 9H 2 O was dissolved in 100 mL of deionized water to obtain a stable, transparent, homogeneous solution.
[0052] (2) At room temperature, nitrogen aeration and vigorous stirring, the above homogeneous solution was added dropwise to a solution containing 5.2995 g Na 2 CO 3 and 2g of streptomycin waste residue in 100mL of a mixed solution (the solvent is deionized water), and a 4mol / L NaOH solution is used to maintain the pH value of the system at 10. After the addition is completed, the aging is continued for 12h.
[0053] (3) After aging, the aged mixed solution is filtered and repeatedly washed with deionized water until the pH value of the filtrate is 6-7 (measured by pH test paper). When the filtrate is almost dried, it is washed once with anhydrous ethanol and dried to obtain a precipitate. The obtained precipitate is placed in a beaker containing 200-300 mL of anhydrous ethanol, vigorously stirred for 1-2 hours at room temperature, and then filtered. The filter cake is repeatedly washed with anhydrous ethanol. The obtained filter cake is placed in a 60°C blast oven, dried overnight, and then ground into a powder state to obtain Mn 1 Al 1 -LDH-Str hydrotalcite-like
[0054] (4) The dried powder was placed in a muffle furnace and calcined under oxygen-limited conditions. After calcination at 400 °C for 5 h, the biochar-based catalyst, Mn 1 Al 1 O z -Str-2 catalyst.
[0055] The biochar-based catalyst prepared in Example 1 was subjected to XPS analysis, and the results showed that the Mn in the catalyst was Mn 2+ , Mn 3+ and Mn 4+ A mixed form of three valence states, and Mn 2+ and Mn 3+Accounting for 78.6%, Mn 4+ Proper amount of Mn 4+ The catalyst has excellent denitrification performance and N 2 Selective.
[0056] Comparative Example 1: MnAlO z Preparation method of BC catalyst
[0057] In order to better evaluate the Mn 1 Al 1 O z -Str-2 catalyst denitrification performance, using conventional loading method to load MnAlO onto biochar (BC) derived from streptomycin waste residue z / BC catalyst. First, biochar (BC) derived from streptomycin waste residue was prepared by calcination at 400℃. 4mL of the prepared 0.2g / mL mixed solution of manganese nitrate and aluminum nitrate (the molar ratio of manganese nitrate to aluminum nitrate in the solution was 1:1) was loaded onto 2g of BC carrier by equal volume impregnation method, placed in an 80℃ forced air drying oven, dried for 12 hours, and the dried powder was placed in a muffle furnace and calcined at 400℃ for 5 hours to obtain MnAlO z The / BC catalyst was used as a control catalyst.
[0058] MnAlO prepared in Comparative Example 1 z / BC catalyst was subjected to XPS analysis, and the results showed that the Mn in the catalyst was Mn 2+ , Mn 3+ and Mn 4+ A mixed form of three valence states, and Mn 2+ and Mn 3+ Accounting for 85.3%, Mn 4+ It accounts for 14.7%.
[0059] Comparative Example 2: Mn 1 Al 1 O z Method for preparing catalyst
[0060] (1) 5.81 mL of Mn(NO 3 ) 2 、9.3783gAl(NO 3 ) 3 9H 2 O was dissolved in 100 mL of deionized water to obtain a stable, transparent, homogeneous solution.
[0061] (2) At room temperature, nitrogen aeration and vigorous stirring, the above homogeneous solution was added dropwise to a solution containing 5.2995 g Na 2 CO 3100mL solution (solvent is deionized water), and 4mol / L NaOH solution is used to maintain the pH value of the system at 10. After the addition is completed, it is aged for 12h.
[0062] (3) After aging, the aged mixed solution is filtered and repeatedly washed with deionized water until the pH value of the filtrate is 6-7 (measured by pH test paper). When the filtrate is almost dried, it is washed once with anhydrous ethanol and dried to obtain a precipitate. The obtained precipitate is placed in a beaker containing 200-300 mL of anhydrous ethanol, vigorously stirred for 1-2 hours at room temperature, and then filtered. The filter cake is repeatedly washed with anhydrous ethanol. The obtained filter cake is placed in a 60°C blast oven, dried overnight, and then ground into a powder state to obtain Mn 1 Al 1 -LDH type hydrotalcite.
[0063] (4) The dried powder was placed in a muffle furnace and calcined at 400°C for 5 hours to obtain Mn 1 Al 1 O z The catalyst was used as another control catalyst. (That is, the only difference from Example 1 is that the addition of 2 g of streptomycin waste residue in step (2) was omitted, and the remaining steps and parameters were the same as those in Example 1)
[0064] Mn prepared in Comparative Example 2 1 Al 1 O z The catalyst was subjected to XPS analysis, and the results showed that the Mn in the catalyst was Mn 2+ , Mn 3+ and Mn 4+ A mixed form of three valence states, and Mn 2+ and Mn 3+ Accounting for 79.2%, Mn 4+ It accounts for 20.8%.
[0065] Effect verification example 1: Catalyst activity test method
[0066] The catalytic performance test was carried out in a fixed bed microreactor (diameter d = 6 mm) at normal pressure, with a test temperature range of 100-300°C. The sample size was 0.15 g, and the gas composition of the simulated flue gas was: 500 ppm NO x , 500ppm NH 3 , 5% O 2 , Ar as the balance gas. NO in the gas composition before and after the reaction x The samples were analyzed online using a 2.4 M Gas Cell (Parker Technologies) and a Bruker INVENIO S analyzer (Bruker Optics).
[0067] Effect verification example 2: Effects of different metal molar ratios and different quality waste residues on catalyst performance
[0068] The method in Example 1 was used to prepare catalyst materials of hydrotalcite-like materials with different metal ratios and composites of different masses of antibiotic waste residues and different types of antibiotic bacterial residues, wherein the molar ratio of Mn / Al was 1 / 2 to 2 / 1, and the mass of streptomycin waste residue was 0.5 to 4 g. The corresponding catalyst (i.e., the only difference from Example 1 is that the molar ratio of Mn / Al is adjusted to 1 / 2 to 2 / 1; or, the mass of streptomycin waste residue is adjusted to 0.5 to 4 g; or, the type of antibiotic bacterial residue is adjusted to oxytetracycline or gentamicin; the remaining steps and parameters are the same as those in Example 1) and used for laboratory simulation of flue gas, and then the activity test method in Effect Verification Example 1 was used to determine the catalyst performance. The test results (as shown in Tables 1-3) show that the catalysts prepared with different metal ratios and different masses of antibiotic waste residues in the catalyst are effective in treating NO in flue gas. x Different catalytic properties were exhibited during the process. The catalyst prepared when the antibiotic waste residue was streptomycin waste residue and the mass and metal ratio were 2g and 1:1 respectively had the best catalytic performance. When the test temperature was 150℃, Mn 1 Al 1 O z -Str-2 NO x The conversion rate reached 98.04%.
[0069] Table 1 Effect of different mass streptomycin on catalyst performance (calcination temperature is 400℃, test temperature is 150℃)
[0070]
[0071] Table 2 Effect of different metal ratios on catalyst performance (calcination temperature is 400°C, test temperature is 150°C)
[0072]
[0073] Table 3 Effects of different types of antibiotics on catalyst performance (calcination temperature is 400°C, test temperature is 150°C)
[0074]
[0075] Effect verification example 3: Test on the effect of calcination temperature and space velocity on catalyst activity
[0076] The effects of calcination temperature and gas space velocity (GHSV) on catalyst activity are crucial. Different calcination temperatures and GHSV have different effects on the occurrence of redox reactions in the catalyst and the adsorption capacity of gas components. Therefore, in order to determine an optimal calcination temperature and GHSV, Mn 1 Al 1 O z -Str-2 catalyst was tested at different calcination temperatures (calcination temperature was 350-600°C, i.e., the only difference from Example 1 was that the calcination temperature in step (4) was adjusted to 350-600°C, and the other steps and parameters were the same as those in Example 1; the test temperature was 150°C) and GHSV (80,000 and 120,000 h -1 ) was used to treat laboratory simulated flue gas, and then the catalyst performance was determined using the activity test method in effect verification example 1. The test results are shown in Table 4-5, indicating that: Mn 1 Al 1 O z -The optimal calcination temperature of Str-2 catalyst is 400℃ and the GHSV is 80,000h -1 .
[0077] Table 4 Effect of calcination temperature on catalyst performance
[0078]
[0079] Table 5 Effect of space velocity on catalyst performance
[0080]
[0081] Effect verification example 4: Mn 1 Al 1 O z -Str-2, Mn 1 Al 1 O z and MnAlO z Activity test of BC catalyst at different test temperatures
[0082] Temperature testing is crucial in the catalyst activity test. Different test temperatures have different effects on the occurrence of redox reactions in the catalyst and the adsorption capacity of gas components. Therefore, in order to determine the optimal test temperature range, the methods of Example 1 and Comparative Examples 1 and 2 were used to prepare Mn 1 Al 1 O z -Str-2, Mn 1 Al 1 O z and MnAlO z / BC catalyst (calcination temperature of 400℃, test temperature of 100-300℃) was used to treat laboratory simulated flue gas, and then the catalyst performance was measured using the activity test method in effect verification example 1. The test results (as shown in Table 6) show that Mn 1 Al 1 O z -Str-2 has excellent NO at medium and low temperatures x Catalytic reduction performance, when the test temperature is 150 ~ 250 ℃, NO x The conversion rate is higher than 98%. At 150℃, Mn 1 Al 1 O z and MnAlO z / BC's NO x The conversion rates are 95.38% and 37.88% respectively. By comparison, it can be concluded that the catalyst of the present invention has higher activity and wider reaction temperature window.
[0083] Table 6Mn 1 Al 1 O z -Str-2, Mn 1 Al 1 O z and MnAlO z / BC catalyst activity test results (test temperature 100 ~ 300 ℃)
[0084]
[0085] Effect verification example 5: Test of the sulfur and water resistance of the catalyst
[0086] In actual working conditions, sulfur resistance and water resistance are important indicators to measure catalyst performance. Sulfur poisoning and water poisoning are important problems facing catalysts. 2 It mainly reacts with the active components in the catalyst to form sulfates, sulfites, etc., resulting in a reduction in active components and blocking the catalyst pores. Water mainly occupies the active sites of the catalyst, resulting in a decrease in activity. Therefore, the requirements for the catalyst's sulfur and water resistance are essential. 1 Al 1 O z -Str-2 catalyst was used as an example, and its sulfur resistance and water resistance were combined with the MnAlO prepared by the loading method. z / BC catalyst Mn 1 Al 1 O z The catalysts were compared. On the other hand, the regeneration of the catalyst after sulfur and water poisoning was considered. The thermal treatment regeneration method is an effective catalyst regeneration method. 1 Al1 O z -Str-2, Mn 1 Al 1 O z and MnAlO z / BC catalyst was subjected to sulfur and water resistance test and regeneration test as follows:
[0087] The sulfur resistance test of the catalyst was carried out in a fixed bed microreactor (diameter d = 10 mm) at normal pressure. The sample weight was 0.15 g, the gas flow rate was 200 mL / min, and the gas composition of the simulated flue gas was: 500 ppm NO x , 500ppmNH 3 , 100ppmSO 2 , 5% H 2 O, 5% O 2 , Ar as the balance gas. NO in the gas composition before and after the reaction x The samples were analyzed online using a 2.4M Gas Cell (Parker Technologies) and a BRUKER INVENIO S analyzer (Bruker Optics).
[0088] Mn prepared by the method in Example 1 and Comparative Examples 1 and 2 1 Al 1 O z -Str-2, Mn 1 Al 1 O z and MnAlO z / BC catalyst (calcination temperature is 400℃) was used to treat laboratory simulated flue gas, and then the sulfur resistance of the catalyst was measured using the above sulfur resistance test method. The test results are shown in Table 7. Compared with the Mn prepared by the methods of Comparative Examples 1 and 2, 1 Al 1 O z and MnAlO z Compared with BC, Mn 1 Al 1 O z -Str-2 catalyst exhibits good resistance to SO at 150℃ 2 At 100ppm SO 2 In the presence of MnAlO z / BC and Mn 1 Al 1 O z NO x The conversion rates were 21.04% and 70.06%, respectively, compared with those without SO 2 Compared with the case of NO x The conversion rates decreased by 16.84% and 25.32%, respectively.1 Al 1 O z -Str-2 catalyst, at 100ppm SO 2 In the presence of NO, at 150°C x The conversion rate was 83.87%, which was comparable to that without SO 2 Compared with the case of SO, it is reduced by 14.17%. 2 It has a great influence on the activity of catalysts prepared by the supported method and single hydrotalcite-like catalysts. 1 Al 1 O z -Str-2 catalyst, SO 2 The effect on catalysts is relatively weak.
[0089] Table 7Mn 1 Al 1 O z -Str-2, Mn 1 Al 1 O z and MnAlO z / BC catalyst sulfur resistance test (test temperature 100 ~ 300 ℃)
[0090]
[0091] In actual industrial flue gas, SO 2 and H 2 O exists at the same time, therefore, the Mn prepared by the methods in Example 1 and Comparative Examples 1 and 2 1 Al 1 O z and MnAlO z The sulfur and water resistance of the catalyst was tested by the above test method. The test results are shown in Table 8. The results show that the MnAlO prepared by the method of Comparative Examples 1 and 2 z / BC and Mn 1 Al 1 O z In comparison, Mn 1 Al 1 O z -Str-2 catalyst performs excellently in NO x Conversion rate, at 100ppm SO 2 +5%H 2 In the presence of O, at 150℃, Mn 1 Al 1 O z -Str-2 catalyst for NO x The conversion rate is 76.4%.z / BC and Mn 1 Al 1 O z Catalyst NO x The conversion rates were 16.4% and 62.6%, respectively. 2 Preparation of MnAlO by water-supported method z / BC and Mn 1 Al 1 O z The catalyst has a greater impact, while SO 2 and water to Mn 1 Al 1 O z -Str-2 catalyst has a relatively weaker effect on its activity, which shows that the catalyst prepared by the present invention has improved anti-poisoning performance while ensuring a higher catalytic activity.
[0092] Table 8Mn 1 Al 1 O z -Str-2, Mn 1 Al 1 O z and MnAlO z / BC's anti-SO 2 +H 2 O activity test (test temperature is 100~300℃)
[0093]
[0094] Effect verification example 6: Mn 1 Al 1 O z -Str-2, Mn 1 Al 1 O z and MnAlO z / BC catalyst regeneration test
[0095] The above anti-SO 2 +H 2 The catalyst was regenerated by heat treatment after 12 hours of O test. The regeneration temperature was 400℃ and the time was 30min. The regenerated catalyst was treated with laboratory simulated flue gas. Then the activity test method in effect verification example 1 was used to measure the catalyst performance. The test results (as shown in Table 9, the test temperature was 150℃) showed that Mn 1 Al 1 O z -Str-2, Mn 1 Al 1 O z and MnAlO zAfter the heat treatment and regeneration, the activity of the catalysts was restored to a certain extent, but not completely, which may be attributed to the loss of active components during the regeneration process. 1 Al 1 O z -Str-2 compared to Mn 1 Al 1 O z and MnAlO z / BC still has high activity, Mn 1 Al 1 O z -Str-2 had an activity of 89.06%, while Mn 1 Al 1 O z and MnAlO z / BC are 73.44% and 28.66% respectively. Combined with the above test on the effect of calcination temperature on catalyst activity, it can be concluded that Mn 1 Al 1 O z -Str-2 has good thermal stability, so relative to Mn 1 Al 1 O z and MnAlO z / BC has higher catalytic activity after thermal treatment and regeneration.
[0096] Table 9Mn 1 Al 1 O z , Mn 1 Al 1 O z -Str-2 and MnAlO z / BC catalyst regeneration test results
[0097]
[0098] Figure 1 a is an X-ray diffraction spectrum, which is respectively Mn before calcination in comparative example 2 1 Al 1 -LDH hydrotalcite (MnAl-LDH in the figure represents Mn 1 Al 1 -LDH), Mn before calcination in Example 1 1 Al 1 -LDH-Str hydrotalcite (MnAl-LDH-Str in the figure represents Mn 1 Al 1 -LDH-Str), Mn obtained after calcination in Comparative Example 2 1Al 1 O z Catalyst, Mn obtained after calcination in Example 1 1 Al 1 O z -Str-2 catalyst. Figure 1 b is the Mn after calcination in Example 1 1 Al 1 O z -TEM-EDS image of Str-2 catalyst.
[0099] Depend on Figure 1 From a, we can see that after the introduction of streptomycin waste residue, relative to Mn 1 Al 1 -LDH hydrotalcite, Mn 1 Al 1 -LDH-Str hydrotalcite-like material hydrotalcite-like characteristic peak only decreased in intensity, and no new characteristic peak appeared, indicating that Mn 1 Al 1 -LDH-Str hydrotalcite-like materials were successfully prepared. After calcination at 400℃ for 5h in a muffle furnace under oxygen-limited conditions, Mn 1 Al 1 O z Catalyst MnAl 2 O 4 and Mn 3 O 4 characteristic peak, and Mn 1 Al 1 O z -Str-2 only has Mn 3 O 4 Characteristic peaks. In addition, TEM-EDS elemental analysis revealed that Mn 1 Al 1 O z -The metal elements in Str-2 are evenly distributed and highly dispersed.
[0100] Compared with single antibiotic waste residue-derived biochar materials and LDHs materials, the biochar-based catalyst prepared by the present invention contains more surface active oxygen species and acid sites, and has excellent redox ability, which can effectively promote NH 3 -SCR reaction, improve the anti-poisoning performance of the catalyst. In addition, the biochar-based catalyst can effectively solve the problem of handling and disposing of a large amount of waste antibiotic residues, can effectively reduce the cost of material production, and is in line with the sustainable development strategy.
[0101] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A biochar-based catalyst for the selective catalytic reduction of NO in flue gas x The application is characterized in that The preparation method of the biochar-based catalyst comprises the following steps: Step 1, dissolving two precursor materials containing Mn and metal N respectively in water to prepare a homogeneous solution; Step 2, adding the homogeneous solution into the alkaline solution containing the waste residue L and maintaining the pH of the reaction system at an alkaline level, aging, and obtaining a mixed solution; Step 3, filtering and washing the mixed solution, and then drying to obtain a hydrotalcite-like composite material containing metals N, Mn and L; Step 4, calcining the hydrotalcite-like composite material containing N, Mn and L to obtain the biochar-based catalyst; The metal N is Al and / or Fe; The waste residue L is at least one of streptomycin waste residue, oxytetracycline waste residue and gentamicin waste residue; The calcination is specifically calcined at 350-600 °C for 5 h under oxygen-limited conditions; Selective catalytic reduction of NO in flue gas x The reaction temperature range is 100~300℃; The Mn in the biochar-based catalyst is Mn 2+ , Mn 3+ and Mn 4+ A mixed form of three valence states.
2. The use according to claim 1, characterized in that: The molar ratio of Mn to metallic N is (0.5~2):
1.
3. The use according to claim 1, characterized in that: The mass ratio of the precursor material containing Mn to the waste slag L is (5~6):(0.5~4).
4. The use according to claim 1, characterized in that: In step 2, the pH of the reaction system is maintained at 8-12.
5. The use according to claim 1, characterized in that: The alkaline solution is a Na2CO3 aqueous solution; the molar ratio of Mn to Na2CO3 in the reaction system is 0.25-1.
Citation Information
Patent Citations
Application of spinel-type oxide and method for catalytic desulfurization and denitrification
CN102836717A
Delafossite type structure CuFeO2 / biochar composite material and preparation method thereof
CN115744999A